2014
DOI: 10.4168/aair.2014.6.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methylprednisolone Pulse Therapy on RefractoryMycoplasma pneumoniaePneumonia in Children

Abstract: PurposeMycoplasma pneumoniae (M. pneumoniae) is one of the most common causes of community-acquired pneumonia in children. The clinical course is typically self-limited and benign; however, rare cases of severe pneumonia can develop despite appropriate antibiotic therapy. We studied the effects of methylprednisolone pulse therapy on severe refractory M. pneumoniae pneumonia in children.MethodsThe clinical effects of methylprednisolone therapy were evaluated retrospectively in 12 children with severe refractory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 21 publications
1
77
1
Order By: Relevance
“…10,11 Clinically, corticosteroids have been used for refractory M. pneumoniae pneumonia and have a dramatic beneficial effect in both children and adults. 2,4,12 Clinicians must be cognizant of children with M. pneumoniae pneumonia at risk for developing refractory or serious illnesses and initiate steroid therapy in a timely fashion. Thus, it is desirable to predict refractory illness as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Clinically, corticosteroids have been used for refractory M. pneumoniae pneumonia and have a dramatic beneficial effect in both children and adults. 2,4,12 Clinicians must be cognizant of children with M. pneumoniae pneumonia at risk for developing refractory or serious illnesses and initiate steroid therapy in a timely fashion. Thus, it is desirable to predict refractory illness as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Although mycoplasmal pneumonia is usually self-limited and benign, some cases may proceed to clinical and radiological deterioration despite appropriate macrolide therapy, which were defined as refractory M. pneumoniae pneumonia (RMPP). The rapidity of response to treatment of RMPP with systemic corticosteroid is satisfying, and it significantly improves the clinical symptoms and outcomes89. Nonetheless, with the use of standard corticosteroid regimens (2 mg/kg/day), fever persists for more than 3 days after treatment in around 20% of children with RMPP10.…”
mentioning
confidence: 99%
“…Our histological finding that macrophages are enriched in infiltrating cells can explain the fact that IL-18 increases in patients with severe M. pneumoniae pneumonia. The use of corticosteroids combined with antibiotic therapy to decrease the inflammatory response -with dramatic beneficial effectshas also been demonstrated in several studies [2][3][4][5][6][7]14]. Our histological study indicated that corticosteroids might be effective against oedema of the alveolar, bronchial and bronchiolar walls, polypoid organizing tissue and cellular bronchiolitis with lymphocytic infiltration.…”
Section: à3mentioning
confidence: 62%
“…It is well known that some cases develop into severe pneumonia [2][3][4][5][6][7]. Several studies have demonstrated that an excessive host cellular response, especially with respect to IL-18, plays a critical role in the development of serious pulmonary manifestations [8][9][10][11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation